Analysis of the Architecture of the Tanjung Mulia Grand Mosque in Medan as an Islamic and Cultural Heritage - Aprilia, Fasya Dwi; Tanjung, Muaz (Journal La Sociale, 2025)
This study analyzes That architecture characteristics of the Tanjung Mulia Jami' Mosque in Medan, with a focus on design element he realize. Mosque feature different architecture element like an octagonal tower, multi -storey pyramidal roofs, and Malay -Islamic ornaments That reflect That local cultural acculturation culture based on Islamic values. This research uses a descriptive approach. qualitative method through interviews, field observations, and literature reviews. Research findings reveal That That mosque combine Islamic, Malay and colonial elements architecture. Features such as domes, minarets, mihrabs, and Arabic calligraphy strengthen its Islamic identity. The building design Also adapt to That tropical climate through That utilization of ventilation and natural lighting. Spatial planning not only supports religious function But Also functions as a social space For That community. Jami' Mosque functions not only as a place of worship But also as a cultural heritage site That reflect That a blend of local and Islamic values. Its preservation is important to guard architecture identity and history Medan heritage.